DIRECT INSTRUCTION LEARNING MODEL: A LITERATURE REVIEW - linda riyana linda (Teaching and General Education Studies, 2026)
This article aims to conduct an in-depth analysis of the direct instruction learning model through a literature review. The review included various references, including educational theory books and recent scientific journal articles, to examine the basic concepts, theoretical foundations, implementation steps (syntax), advantages and limitations, and relevance in today's educational context. Direct instruction is viewed as a systematic and structured learning model, emphasizing the explicit delivery of material by the teacher through sequential stages, from the presentation of learning objectives to independent practice activities. The study results indicate that this model is effective in improving understanding of fundamental concepts and mastery of procedural skills due to its emphasis on demonstration activities, guided practice, and continuous feedback. However, when applied alone, this model tends to be less than optimal in developing student creativity and active engagement. Therefore, direct instruction remains relevant for situational use and is recommended for integration with other learning models to achieve more comprehensive educational goals.